Unexpected PD‐L1 immune evasion mechanism in TNBC, ovarian, and other solid tumors by DR5 agonist antibodies - Tanmoy Mondal; Gururaj N Shivange; Rachisan GT Tihagam; Evan Lyerly; Michael Battista; Divpriya Talwar; Roxanna Mosavian; Karol Urbanek; Narmeen S Rashid; J Chuck Harrell; Paula D Bos; Edward B Stelow; et al. (EMBO Molecular Medicine, 2021)
Abstract Lack of effective immune infiltration represents a significant barrier to immunotherapy in solid tumors. Thus, solid tumor‐enriched death receptor‐5 (DR5) activating antibodies, which generates tumor debulking by extrinsic apoptotic cytotoxicity, remains a crucial alternate therapeutic strategy. Over past few decades, many DR5 antibodies moved to clinical trials after successfully controlling tumors in immunodeficient tumor xenografts. However, DR5 antibodies failed to significantly improve survival in phase‐II trials, leading in efforts to generate second generation of DR5 agonists to supersize apoptotic cytotoxicity in tumors. Here we have discovered that clinical DR5 antibodies activate an unexpected immunosuppressive PD‐L1 stabilization pathway, which potentially had contributed to their limited success in clinics. The DR5 agonist stimulated caspase‐8 signaling not only activates ROCK1 but also undermines proteasome function, both of which contributes to increased PD‐L1 stability on tumor cell surface. Targeting DR5‐ROCK1‐PD‐L1 axis markedly increases immune effector T‐cell function, promotes tumor regression, and improves overall survival in animal models. These insights have identified a potential clinically viable combinatorial strategy to revive solid cancer immunotherapy using death receptor agonism.